Pengaruh Senam Ergonomi Dalam Mencegah Musculoskeletal Disorders (MSDS) pada Ibu Rumah Tangga RT 11 Kelurahan Bagan Pete - Aswin, Budi; Sari, Rumita Ena; Hubaybah, Hubaybah; Ibnu, Ismi Nurwaqiah; Arsa, Daniel (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Safety at home is an important aspect that needs to be considered to protect yourself and your family. Although often considered less risky than formal workplaces, homes also have potential hazards that can threaten safety and health. Around 1.71 billion people worldwide experience musculoskeletal disorders (MSDs). One of the non-pharmacological treatments that can be applied for MSDs is ergonomic exercise. However, the low understanding and awareness of housewives about ergonomic hazards due to daily activities is a problem. Many mothers carry out housework without adequate knowledge of ergonomic principles, thus increasing the risk of MSDs. Therefore, it is important to increase public awareness of the benefits of ergonomic exercises, which can help maintain health and minimize the risk of musculoskeletal disorders during activities at home. This study aims to analyze the effect of ergonomic exercises in preventing musculoskeletal disorders (MSDs) in housewives in RT 11 Bagan Pete Village. Results showed an increase in knowledge of ergonomic work hazards, with a probability value of p < 0.001, which indicates significance below 0.05. The mean pre-test score of participants was 10.13 (SD 5.476), while the mean post-test score increased to 18 (SD 1.259). In addition, the change in musculoskeletal complaints after stretching was also significant, with a p-value of 0.002. This shows that stretching has a positive impact in reducing musculoskeletal complaints among housewives. In conclusion, the ergonomic exercise service program not only increases knowledge and skills regarding good posture, but also provides more energy and reduces muscle pain. This activity succeeded in raising awareness of the importance of ergonomics in daily activities, which is expected to reduce the risk of injury due to household chores.